Contemporary perspectives on language policy and literacy instruction in early childhood education - Saracho, Olivia N.; Spodek, Bernard (Contemporary perspectives in early childhood education., 2004)
In this anthology, Saracho (curriculum and instruction, University of Maryland) and Spodek (early childhood education, University of Illinois) present work reviewing the current state of knowledge on the education of students who are not fully proficient in English. The editors attempt to move beyond the narrow focus of language instruction that has dominated education and policy discussions to examine individual, social, and instructional factors that affect English language learners.